Control Strategies Applied to Wave Energy Converters: State of the Art - Aleix Maria-Arenas; Aitor J. Garrido; Eugen Rusu; Izaskun Garrido (Energies, 2019)
Wave energy’s path towards commercialization requires maximizing reliability, survivability, an improvement in energy harvested from the wave and efficiency of the wave to wire conversion. In this sense, control strategies directly impact the survivability and safe operation of the device, as well as the ability to harness the energy from the wave. For example, tuning the device’s natural frequency to the incoming wave allows resonance mode operation and amplifies the velocity, which has a quadratic proportionality to the extracted energy. In this article, a review of the main control strategies applied in wave energy conversion is presented along their corresponding power take-off (PTO) systems.